Programação linear no planejamento agregado de produção e vendas de uma indústria siderúrgica - Jose Cecilio Moreira Junior (2009)
This work deals with the problem of elaboration of the Aggregate Production and Sales Planning applied in a steel plant producing special steels. This type of problem is studied broadly in the literature and the first works, with the use of Operational Research, date back to the beginning of the decade of 50. The approached steelworks has a quite complex configuration due to the production of types of steels that have different production processes sharing the same equipment. The basic proposal of the problem is the establishment of the mixture of products sold that leads to the best managerial result. In order to obtain this, the capacities of the plant and the necessary stocks should be safeguard to guarantee the level of services aimed at by the company. The involved products are among the highest quality of metallurgy and the planning of the production of the company operates with the system made-to-order for meeting demands. In the literature there are models with several techniques and objectives function. In this work, Linear Programming is adopted and the objective function is maximization of the contribution margin. The principal challenge was to reconcile the use of the equipment in different production routes. The work is organized into four copies. The first makes an introduction for contextualization of the problem in the corporate atmosphere. The first chapter is a bibliographical revision taking in the principal works found on the subject and it presents some extracted mathematical models of the same. In the second chapter, the presentation of the ambience is presented where the problem was dealt with and the objectives and challenges there found. The chapter ends with the presentation of the mathematical modeling. In the following chapter the results found in the several executed tests are presented found in the several executed tests. In the last part, a conclusion is made and proposals of the future development for improvement of the model and its integration with the production programming.